Evaluating the Prevention Benefit of HCV Treatment: Modeling the SToP‐C Treatment as Prevention Study in Prisons. Issue 5 (22nd August 2021) - Lim, Aaron G.; Stone, Jack; Hajarizadeh, Behzad; Byrne, Marianne; Chambers, Georgina M.; Martin, Natasha K.; Grebely, Jason; Dore, Gregory J.; Lloyd, Andrew R.; Vickerman, Peter
Abstract : Background and Aims: Between 2014 and 2019, the SToP‐C trial observed a halving in HCV incidence in four Australian prisons following scale‐up of direct‐acting antiviral (DAA) therapy. However, the contribution of HCV treatment to this decline is unclear because the study did not have a control group. We used modeling to consider this question. Approach and Results: We parameterized and calibrated a dynamic model of HCV transmission in prisons to data from each SToP‐C prison on incarceration dynamics, injecting drug use, HCV prevalence trends among prison entrants, baseline HCV incidence before treatment scale‐up, and subsequent HCV treatment scale‐up. The model projected the decrease in HCV incidence resulting from increases in HCV treatment and other effects. We assessed whether the model agreed better with observed reductions in HCV incidence overall and by prison if we included HCV treatment scale‐up, and its prevention benefits, or did not. The model estimated how much of the observed decrease in HCV incidence was attributable to HCV treatment in prison. The model projected a decrease in HCV incidence of 48.5% (95% uncertainty interval [UI], 41.9‐54.1) following treatment scale‐up across the four prisons, agreeing with the observed HCV incidence decrease (47.6%; 95% CI, 23.4‐64.2) from the SToP‐C trial. Without any in‐prison HCV treatment, the model indicated that incidence would have decreased by 7.2% (95% UI, −0.3 to 13.6). This suggests that 85.1% (95% UI, 72.6‐100.6) of the observed halving in incidence was from HCV treatment scale‐up, with the remainder from observed decreases in HCV prevalence among prison entrants (14.9%; 95% UI, −0.6 to 27.4). Conclusions: Our results demonstrate the prevention benefits of scaling up HCV treatment in prison settings. Prison‐based DAA scale‐up should be an important component of HCV elimination strategies.